Effect of TMAO on the incidence and prognosis of cerebral infarction: a systematic review and meta-analysis - Wang, Lin; Nan, Yinan; Zhu, Wenhao; Wang, Shaoqing (Frontiers in Neurology, 2024)
Objective: To evaluate the effect of trimethylamine oxide (TMAO) on the incidence and prognosis of cerebral infarction.We searched PubMed, Embase, and Cochrane databases for all clinical studies on the association of TMAO with cerebral infarction incidence and prognosis from inception to April 2023.A systematic review and meta-analysis were conducted using the Meta-analysis of observational studies in epidemiology (MOOSE) declaration list. The Newcastle-Ottawa Scale (NOS) was used to assess the study's quality. The present study protocol was registered on the PROSPERO database with the ID: CRD42023459661. The extracted data included the OR value of the effect of TMAO on the incidence and prognosis of cerebral infarction, the HR value between TMAO and underlying diseases, the RR value, 95% confidence intervals, and the AUC value of TMAO in the prediction model of cerebral infarction.Results: Fifteen studies including 40,061 patients were included. All the patients were from China or Germany. The TMAO level was significantly correlated with the Modified Rankin Score (mRS) three months after the onset of cerebral infarction (OR, 1.581; 95% CI, 1.259-1.987; P <0.01). The TMAO level was significantly correlated with the rate of first-time incidence and recurrence of